2017
DOI: 10.1002/dvdy.24579
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal soma controls ovarian follicle proliferation through Gsdf in zebrafish

Abstract: Background Aberrant signaling between germ cells and somatic cells can lead to reproductive disease and depends on diffusible signals, including TGFB-family proteins. The TGFB-family protein Gsdf (gonadal soma derived factor) controls sex determination in some fish and is a candidate for mediating germ cell/soma signaling. Results Zebrafish expressed gsdf in somatic cells of bipotential gonads and expression continued in ovarian granulosa cells and testicular Sertoli cells. Homozygous gsdf knockout mutants d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 191 publications
(266 reference statements)
3
72
0
Order By: Relevance
“…It is known that targeted disruption of gsdf in medaka causes abnormal folliculogenesis associated with sterility [56]. In zebrafish, Gsdf may have a role in regulating ovarian follicle maturation and expression of genes involved in steroid biosynthesis, obesity, diabetes, and female fertility [57]. Lack of Gsdf in medaka has been linked to a dysregulation of oocyte development [58].…”
Section: Gsdfmentioning
confidence: 99%
“…It is known that targeted disruption of gsdf in medaka causes abnormal folliculogenesis associated with sterility [56]. In zebrafish, Gsdf may have a role in regulating ovarian follicle maturation and expression of genes involved in steroid biosynthesis, obesity, diabetes, and female fertility [57]. Lack of Gsdf in medaka has been linked to a dysregulation of oocyte development [58].…”
Section: Gsdfmentioning
confidence: 99%
“…We show here that this phenotype correlates with multiple and ectopic Taz expressing MCs. The study of the tight communication established between the oocyte and FCs during the zebrafish folliculogenesis have shed lights into the underlying mechanism regulating oocyte development progression and survival (Li and Ge, 2011;Yan et al, 2017). However, the identification of reciprocal signaling exchange governing micropyle biogenesis has not been reported yet.…”
Section: Taz Functions As a Major Regulator Of The Micropylar Cell Fatementioning
confidence: 99%
“…In this study we found that gsdf is highly expressed in females and males, with specific transcript localization in granulosa and Sertoli cells, respectively. Likewise, expression of gsdf in the same cell types has been observed in several fish species including rainbow trout (Oncorhynchus mykiss), medaka In zebrafish, Gsdf may have a role in regulating ovarian follicle maturation and expression of genes involved in steroid biosynthesis, obesity, diabetes, and female fertility [57]. Lack of Gsdf in medaka has been linked to a dysregulation of oocyte development [58].…”
Section: Gsdfmentioning
confidence: 95%